2008
DOI: 10.1111/j.1540-8191.2007.00547.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Biventricular Pacing Postcardiopulmonary Bypass in Patients with Reduced Ejection Fraction

Abstract: In patients with low EF, BiV pacing immediately after CPB significantly improves LV systolic function and cardiac output, and suggests significantly improved diastolic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…This may explain the beneficial effect of BiV pacing compared with AAI pacing in our study compared with previous trials [6, 8, 9]. There are only limited data on postoperative VV optimization after cardiac surgery.…”
Section: Discussionsupporting
confidence: 47%
“…This may explain the beneficial effect of BiV pacing compared with AAI pacing in our study compared with previous trials [6, 8, 9]. There are only limited data on postoperative VV optimization after cardiac surgery.…”
Section: Discussionsupporting
confidence: 47%
“…However, aside from limited examination of lead location [18,24,28] and VVD [25], formal optimization of BiVP had not been attempted in temporary pacing. We initiated the Biventricular Pacing after Cardiac Surgery (BiPACS) trial hoping that optimization would improve the results of temporary postoperative BiVP and improve understanding of high nonresponse rates in permanent CRT [2931].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, this is not associated with changes in myocardial energy demand (21), unlike most inotropic agents, which improve contractility at the expense of increased oxygen consumption and energy store depletion (29). Acute functional benefit without increased energy cost makes BiVP an excellent option for treatment of postoperative ventricular failure, and initial studies have shown its utility after cardiac surgery (14,20,23,24,33).…”
mentioning
confidence: 99%